A Culturally Proficient Response to LGBT Communities: A Guide for Educators - Martirosyan, Nara (Journal of International Students, 2014)
In recent years, educators are challenged to work with more diverse student population than ever before. While the benefits of diversity should never be underestimated, it is also important to acknowledge challenges created by diversity and the need of guidance to educators on how to be culturally responsive to the needs of their diverse students. A Culturally Proficient Response to LGBT Communities (Lindsey, Nuri-Robins, Terrell, & Lindsey, 2013) is a valuable guide for educators working with LGBT (lesbian, gay, bisexual, and transgender) students. This book is a useful resource for those who are interested in learning more about LGBT communities and becoming familiar with their needs and challenges in today's society.